The effect of plastic anisotropy on flange wrinkling behaviour during sheet metal forming - Naziri, H. (College of Aeronautics, 1967)
During the drawing of sheet metal between a die and a blankholder, compressive hoop-stresses are developed which attempt to thicken or wrinkle the flange. Previous work on this behaviour has ignored any effects due to normal or planar plastic anisotropy. In this paper it is shown that the blankholder pressure necessary to suppress wrinkling increases with decreasing normal anisotropy (r) and increases with increasing planar anisotropy (AO. The approximate plane strain conditions (daz = 0) operating in the flange can be simulated by an edge-notched tensile specimen and this simulation demonstrates the effect of texture hardening and softening upon flange wrinkling behaviour. The results obtained can be interpreted valitatively by the use of anisotropic plasticity theory. The speed of drawing also effects wrinkling, in general, the number of wrinkles decreases with increasing drawing speed.